DelPhi Web Server: A Comprehensive Online Suite for Electrostatic Calculations of Biological Macromolecules and Their Complexes (Communications in Computational Physics, 2013)
Here we report a web server, the DelPhi web server, which utilizes DelPhiprogram to calculate electrostatic energies and the corresponding electrostatic potential and ionic distributions, and dielectric map. The server provides extra servicesto fix structural defects, as missing atoms in the structural file and allows for generation of missing hydrogen atoms. The hydrogen placement and the correspondingDelPhi calculations can be done with user selected force field parameters being either Charmm22, Amber98 or OPLS. Upon completion of the calculations, the user isgiven option to download fixed and protonated structural file, together with the parameter and Delphi output files for further analysis. Utilizing Jmol viewer, the usercan see the corresponding structural file, to manipulate it and to change the presentation. In addition, if the potential map is requested to be calculated, the potentialcan be mapped onto the molecule surface. The DelPhi web server is available fromhttp://compbio.clemson.edu/delphi webserver.